Pengembangan Sistem Informasi Pengelolaan Judul Skripsi dan Tugas Akhir dengan Fitur Deteksi Kemiripan Menggunakan Algoritma Winnowing - Pratama, Nanda Putra Bayu; Mustaqiem, Mustaqiem; Minarni, Minarni (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
The development of information technology has a major impact on almost all aspects of human life, such as in the field of education. Complex college academic activities require an information system that can assist in its management. Skripsi management is part of the university's academic activities that aim to manage data from the process of implementing skripsi activities. Submission of skripsi titles using printed proposals, finding information about skripsi title data stored at universities is relatively difficult, the process of comparing titles based on the examiner's knowledge of existing title data is a problem that must be minimized. A skripsi title submission system is designed that applies the winnowing algorithm in it. With this system, title proposals can be submitted online, there is a data search feature for skripsi titles, the system can provide recommendations for acceptance of the proposed title based on the comparison of the percentage of similarity with the percentage limit of the percentage of accepted similarity that has been determined in the system. The results of the algorithm test show that the winnowing algorithm can be used in calculating the word similarity level by looking for fingerprint similarities in the sentences being compared